Analisis Pelayanan Publik Berbasis Inovasi (E-Government) di Kantor Wilayah Kementrian Agama Provinsi Gorontalo - Yulinar puluhulawa; Arifin Tahir; Fenti Prihatini Tui (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This study aims to analyze how public service based on innovation (E- Government) is implemented at the Regional Office of the Ministry of Religious Affairs of Gorontalo Province, focusing on 1) support, 2) capacity, and 3) benefits. To achieve this objective, qualitative methods were used, with descriptive data analysis. Data collection techniques included observation, interviews, and documentation, employing qualitative descriptive analysis. The findings indicate that the E-Government-based public service innovation carried out by the Regional Office of the Ministry of Religious Affairs of Gorontalo Province involves: 1) support in the form of training for staff on system usage and community outreach to ensure understanding of the SISKOHAT system. Additionally, coordination with system developers was conducted to improve and update the application according to user needs. 2) Capacity refers to several IT tools and systems that support electronic public services; however, frequent technical issues, such as system disruptions or hardware limitations, hinder electronic service delivery. 3) The benefits of SISKOHAT include efficient and integrated management of congregation data, which enhances service delivery to congregants by providing more accurate information.